Smart Trash Management in School - Mazwir, Muizzuddin Nadhir; Mazwir, Nurdina Marissa; Harum, Norharyati (Multidisciplinary Applied Research and Innovation, 2022)
Currently, most schools have minimal resources for a cleaner that manages trash. When the number of student increase, this will also increase the total amount of garbage that can accumulate in these schools. These two factors will contribute to a lack of control to manage trash in the school area. We propose a wireless intelligent trash management system to be implemented in schools to solve this problem. This project aims to assist the school in providing a conducive environment for students at school by implementing an efficient trash management system. Our system is equipped with IoT and wireless technology with an intelligent notification feature. The notification feature will help to notify the cleaner when the trash can reach 80% of its total capacity. This system has been developed with green and low-cost IoT devices. Additionally, we can activate the system from anywhere using the provided interface. In schools, there are many trash cans, and usually, depending on the location of the trash can that is located near the canteen, it fills up very quickly when compared to other trash cans. By using the proposed system, the cleaner will be able to identify which trash can has nearly reached its limit and needs to be emptied. Trash collection can be systematically managed only with the small number of cleaners. This integration ties with SDG7, which supports green and clean technology. Indirectly assist SDG4 to ensure quality education by providing a quality, clean school environment. This system will be easily navigated by the cleaners as it uses a simple and well-known social chat platform.